The Student Perspective: Can the Use of Technologies Transform Learning? - O'DONNELL, EILEEN (Information Science Reference (an imprint of IGI Global), 2010)
This chapter explores students? perspectives on the transformations that the use of technology has brought to higher education. The use of technologies in higher education facilitates flexible learning environments but the benefits to students who engage with these technologies will only be realised if the design is pedagogically sound. The pedagogic approach employed by lecturers when designing their e-learning platforms or learning management systems has the capability to transform learning. The author?s discipline is Information Technology and Business Information Systems; from experience and case studies there is ample evidence to suggest that the use of technology does not always necessarily meet user requirements. Students are the end users of the technologies that educators use to enhance students? learning experiences. This chapter was undertaken to obtain students? perspectives (as the end users) on the uses of technologies in higher education to assist educators in improving the pedagogical design of their e-learning platforms. The responses received from students clearly indicate they are of the opinion that the use of technologies in higher education beneficially transforms learning but will never replace lecturers. In essence, the benefits that can be achieved through the use of technologies are totally dependent on the ways they are employed pedagogically by lecturers.
PUBLISHED
Keywords: e-learning